Dynamics of a spherical body shedding from a hypersonic ramp. Part 2. Viscous flow. (16th November 2020) - Butler, C. S.; Whalen, T. J.; Sousa, C. E.; Laurence, S. J.
Abstract: Abstract : The separation dynamics of a sphere released from the surface of a ramp into a hypersonic flow is investigated, focusing on the influence of the ramp boundary layer on the sphere behaviour. First, numerical simulations are conducted of a sphere interacting with an isolated high-speed boundary layer to determine the influence on the sphere force coefficients as the sphere diameter and wall-normal location are varied. It is found that the lift coefficient is strongly affected by the near-wall interactions, becoming increasingly negative as the ratio of the sphere radius to boundary-layer thickness, $r/\delta$, is decreased. These results are combined with force coefficients derived from simulations of the sphere interacting with the ramp-generated oblique shock to enable numerical predictions of the sphere trajectories for a $10^{\circ }$ ramp at Mach 6 (using a similar decoupled approach to Part 1 of this work). It is found that the three trajectory types of the inviscid situation – shock surfing, ejection followed by re-entrainment within the shock layer and direct entrainment – also characterize the sphere behaviour here. Their relative prevalence, however, is influenced by the sphere size: for smaller values of $r/\delta$, direct entrainment dominates because of the wall suction, while shock surfing and then ejection/re-entrainment become increasingly likely at larger values of $r/\delta$ . Increasing the ramp angle and/or the free-stream Mach number reduces the relative influence of the boundary-layer interactions. Finally, experiments are conducted using free-flying spheres released from a ramp surface in a hypersonic shock tunnel, confirming the major trends predicted numerically.